2014
DOI: 10.1074/jbc.m114.591339
|View full text |Cite
|
Sign up to set email alerts
|

New Selective Peptidyl Di(chlorophenyl) Phosphonate Esters for Visualizing and Blocking Neutrophil Proteinase 3 in Human Diseases

Abstract: Background: Proteinase 3 activity is poorly controlled by physiological inhibitors, and its biological function is not well understood. Results:We have designed irreversible phosphonate inhibitors based on structural differences between proteinase 3 and elastase. Conclusion: They selectively inhibit proteinase 3 in biological fluids and can act as activity-based probes. Significance: These inhibitors will help clarify proteinase 3 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 51 publications
(69 reference statements)
1
53
0
Order By: Relevance
“…Extravidin-peroxidase Detection of Active PR3-Active PR3 in PLB-985, HL-60, and neutrophil lysates was detected using selective PR3 activity-based probe Bt-[PEG] 66 -PYDA P (O-C 6 H 4 -4-Cl) 2 (31). The volumes of lysates were adjusted so that the final concentration of PR3 was 20 nM and incubated with Bt-[PEG] 66 -PYDA P (O-C 6 H 4 -4-Cl) 2 (250 nM final) for 30 min at 37°C in PBS.…”
Section: Measurements Of Protease Activities In Cell Lysates and Lungmentioning
confidence: 99%
“…Extravidin-peroxidase Detection of Active PR3-Active PR3 in PLB-985, HL-60, and neutrophil lysates was detected using selective PR3 activity-based probe Bt-[PEG] 66 -PYDA P (O-C 6 H 4 -4-Cl) 2 (31). The volumes of lysates were adjusted so that the final concentration of PR3 was 20 nM and incubated with Bt-[PEG] 66 -PYDA P (O-C 6 H 4 -4-Cl) 2 (250 nM final) for 30 min at 37°C in PBS.…”
Section: Measurements Of Protease Activities In Cell Lysates and Lungmentioning
confidence: 99%
“…In addition, there is a charged arginyl residue at position 217 in HNE in the vicinity of S4, whereas it is an Ile in PR3. Our recent study using single-residue mutant PR3 with Arg at position 217 (PR3I217R) revealed that Ile217 in the vicinity of the S4 pocket greatly influences the substrate specificity of PR3 (Guarino et al, 2014).…”
Section: B Substrate Binding Sitesmentioning
confidence: 99%
“…This compound is a highly useful tool to identify soluble active PR3 in biologic samples, such as inflammatory lung secretions and the urine of patients with bladder cancer. The same compound can also be taken to visualize intracellular PR3 and PR3 m on activated neutrophils (Guarino et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations